2019
DOI: 10.1073/pnas.1913278116
|View full text |Cite
|
Sign up to set email alerts
|

ROS-mediated PI3K activation drives mitochondrial transfer from stromal cells to hematopoietic stem cells in response to infection

Abstract: Hematopoietic stem cells (HSCs) undergo rapid expansion in response to stress stimuli. Here we investigate the bioenergetic processes which facilitate the HSC expansion in response to infection. We find that infection by Gram-negative bacteria drives an increase in mitochondrial mass in mammalian HSCs, which results in a metabolic transition from glycolysis toward oxidative phosphorylation. The initial increase in mitochondrial mass occurs as a result of mitochondrial transfer from the bone marrow stromal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 42 publications
1
89
0
Order By: Relevance
“…The bone marrow microenvironment, and particularly BMSCs, provide a special niche and secrete soluble factors that support the survival, differentiation, and proliferation of hematopoietic cells. Mitochondrial transfer from stromal cells into blood stem cells is required for the rapid generation of leukocytes in response to pathogen infection (21). A previous study showed that bone marrow stromal cells are a novel target for RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The bone marrow microenvironment, and particularly BMSCs, provide a special niche and secrete soluble factors that support the survival, differentiation, and proliferation of hematopoietic cells. Mitochondrial transfer from stromal cells into blood stem cells is required for the rapid generation of leukocytes in response to pathogen infection (21). A previous study showed that bone marrow stromal cells are a novel target for RSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Cx43 also represents an alternative system of cell communication in the stem cell niche and allows the exchange of small molecules and organelles between HSC and the BMME. In a recent study, Mistry et al demonstrated that in response to emergency granulopoiesis, ROS-induced oxidative stress opens the Cx43 GJ channel via PI3K-Akt activation and enables mitochondria transfer from BMSC to HSC [142]. Our unpublished findings further suggest that the Cx43 in HSC, through transfer of healthy mitochondria from HSC to stromal cells, maintains the energetic balance of BMSC, and positively regulates BM mesenchymal and hematopoietic regeneration in myeloablative recipients [143], however further investigations are required to identify the trigger signal(s) involved in the mitochondria trafficking and whether cells with the transferred mitochondria intrinsically reprogram myeloablative hematopoiesis, or if it depends on cues from the surrounding microenvironment.…”
Section: Bone Marrow Macrophagesmentioning
confidence: 99%
“…Transfer of mitochondria was also described in the immune system to combat bacterial infections [ 31 ]. The presence of pathogens inside immune cells is usually accompanied by a switch from glycolytic metabolism to OXPHOS as a means of triggering a fast anti-microbial response [ 32 ]. A striking example of infection-induced metabolic switch is seen in macrophages during acute respiratory distress syndrome, when macrophages are fed additional mitochondria by surrounding mesenchymal stem cells (MSCs), boosting their anti-inflammatory and phagocytic capacity [ 31 ].…”
Section: Means Of Mitochondrial Transfermentioning
confidence: 99%
“…Acquiring new mitochondria in the bone marrow niche was recently suggested as a way by which leukemic cells can achieve drug resistance [ 22 , 23 , 37 ]. Up to date, mitochondrial transfer was observed in several types of hematological malignancies, where it seems to have a pro-tumor function [ 32 , 33 , 61 ].…”
Section: Mitochondrial Transfer In Hematological Malignanciesmentioning
confidence: 99%